Association between sodium intake and urinary fractional albumin and immunoglobulin g excretion in chronic nondialytic renal disease: A prospective longitudinal study - Martinez, Marila Gaste [UNESP]; Dos Santos Silva, Vanessa [UNESP]; Do Valle, Adriana Polachini [UNESP]; De Oliveira, Rogério Carvalho [UNESP]; Banin, Vanessa Burgugi [UNESP]; Hokama, Newton Key [UNESP]; Martin, Luis Cuadrado [UNESP] (Karger Publishers, 2019)
Background/Aims: Previous studies reported that fractional clearance of urinary proteins is better than total proteinuria in predicting chronic kidney disease (CKD) progression. However, the role of sodium in the fractional excretion of proteins has not been established. We aimed to evaluate the association between sodium intake and fractional albumin and immunoglobulin G (IgG) excretion in nondialytic CKD. Methods: We did a longitudinal, observational, and prospective study that included CKD patients aged 18-80. Included patients performed basal routine laboratory evaluations, urinary sodium excretion, and fractional albumin and IgG excretion that were repeated after 6-month of follow-up. Results: We evaluated 84 patients, mean age 55 ± 15.6 years, 40 women, and 74 whites. The change of estimated sodium intake had an association with the change of fractional albumin (R = 0.54; p < 0.001) and IgG (R = 0.56; p < 0.001) excretion in univariate analysis (increases in sodium intake were paralleled by increases in albumin and IgG excretion fractions). This association was maintained in a multiple generalized linear model even after adjusting for age and for changes in blood pressure, urinary potassium, protein intake, and blood glucose. Conclusion: In CKD patients, changes in estimated sodium intake were associated with changes in the fractional albumin and IgG excretion regardless of confounding factors. Findings of this study support the idea that reducing salt intake, and consequently, albumin and IgG fractional excretions could help to slow CKD progression. This hypothesis must be tested in long-term interventional studies.
Keywords: Nondialytic chronic renal disease; Proteinuria; Urinary sodium